Four Rs Framework for the development of a digital twin: The implementation of Representation with a FDM manufacturing machine. (April 2022) - Osho, John; Hyre, Anna; Pantelidakis, Minas; Ledford, Allison; Harris, Gregory; Liu, Jia; Mykoniatis, Konstantinos
Abstract: This work considers the conceptualization and design of a 4 Rs framework for creating a general purpose, modular Digital Twin. The 4 Rs, correspond to the 4 different phases of a Digital Twin implementation, namely Representation, Replication, Reality, and Relational. Representation is about understanding the physical system, its behavior, actions, components, relationships and describing the significant features for the identified use case as data and algorithms. Replication duplicates the chosen components/variables in a virtual environment from a set of inputs identified in Representation. Reality employs machine learning to produce a virtual device that runs independent of the physical device with the ability to make predictions, enhance models, provide alternative scenarios and optimizations. Reality enhances the virtual system to become autonomous and self-aware with the ability to make decisions and take corrective actions. We introduce these phases and outline their core elements and principles. We showcase the implementation of phase 1, Representation, using a Fused Deposition Modeling (FDM) additive manufacturing machine via temperature and position sensors. We evaluate their precision in representing the actual FDM machine and lay the foundation work for the implementation of the 4R framework in our next work.